Outcome of Experienced Based Learning (Field Trip) As a Learning Technique in Gaining Knowledge among Graduate and Post Graduate Nursing Students. - G., Malarvizhi; Glory, H.; Rajeswari, S.; Vasanthi, Bindu C (Journal of Health and Allied Sciences NU, 2017)
Education brings changes in behavior of the individual in a desirable manner. It aims at all round development of an individual to become mature, self-sufficient, intellectually, culturally refined, socially efficient and spiritually advanced. In experience- based is that the experience of the learner occupies central place in all considerations of teaching and learning. A key element of experience-based learning is that learners analyze their experience by reflecting, evaluating and reconstructing it in order to draw meaning from it in the light of prior experience. The main aim of the study is to assess the knowledge of nursing students before and after Experience based learning and to determine the attitude of EBL at the end of the field trips. A quasi Experimental research design was adopted. Sample free technique was used to select the 90 B.sc and M.sc (N) students. The data was collected by using semi structured knowledge questionnaire. Inferential and descriptive statistics was used to analyze the data. There was a significant difference in pre test and post test mean score (t= 15.98 at p<0.001). A weak positive correlation was found between post- test knowledge and attitude. There is a significant improvement in knowledge of students in various child welfare services among the present students (c =3.18±.421) than the previous year (c=2.86 ±.371).
Keywords: Experience based learning; Field Trip; Child welfare Agencies